Anionic precursor-mediated morphology-controlled synthesis of ZnS nanostructures: Morphology-dependent tunable photoluminescence in the visible region and pulsed laser-induced efficient reduction of Cr(VI). Issue 10 (1st August 2016) - Kim, Yujin; Amaranatha Reddy, D.; Park, Hanbit; Kim, Tae Kyu
Abstract: Developing a green and convenient synthesis protocol for modification of the morphology of ZnS nanostructures is of great interest but remains a challenge. Herein, a strategy is proposed for tuning the morphology of ZnS nanostructures using different anionic precursors without addition of any organic surfactants or templates. The role of anionic precursors in determining the morphologies is investigated, and a possible growth mechanism involving oriented aggregation and the Ostwald ripening process is proposed. The as-synthesized ZnS nanostructures exhibit outstanding tunable photoluminescence in the visible region depending on the morphology and excitation wavelength. Additionally, the photocatalytic reduction of aqueous Cr(VI) under pulsed irradiation was studied using ZnS catalysts of various nanostructure morphologies in order to study the influence of morphology on the photocatalytic activity of ZnS nanostructures. The analysis revealed that rice grain-shaped ZnS nanostructures exhibit more efficient photocatalytic Cr(VI) reduction compared to other nanostructures. This work also investigated the dependence of the rate of Cr(VI) reduction on the pulsed laser power, pH, and Cr (VI) concentration. The results presented herein should provide a new approach for designing ZnS nanostructures with different morphologies for application in light emitting diodes (LEDs) and water purification systems.